The Evolution of Psychological Realism in the 19th Century English Novel: Depths of Character and Interior Life (The International Journal of Educational Sciences and Arts, 2025)
This article examines the evolution of psychological realism in the 19th-century English novel, focusing on how key novelists developed techniques to explore complex interior lives, ethical dilemmas, and social constraints. Authors such as Jane Austen, Charles Dickens, George Eliot, and Thomas Hardy are examined for their distinct contributions to this shift from plot-driven narratives to character-centered stories that foreground nuanced psychological experiences. The study traces early instances of psychological realism in Austen’s works, where subtle character introspection and social commentary serve as precursors to later, more intricate explorations of the mind. It further investigates Dickens’s portrayal of the common man’s inner turmoil, Eliot’s intellectual depth in moral realism, and Hardy’s tragic consciousness, showing how each novelist employed unique narrative techniques to convey their characters' interiority and societal challenges. Drawing on narratology and literary history, this article analyzes the evolution of specific literary devices—such as free indirect discourse, symbolism, and setting—as methods for enhancing psychological depth. It concludes by arguing that the 19th-century English novel’s engagement with psychological realism marked a pivotal transformation in literary form, profoundly influencing 20th-century writers and solidifying its relevance for contemporary readers (Smith, 2020; Johnson, 2018). This study contributes to broader discussions of literary realism, narrative innovation, and the continuing significance of psychological complexity in literature (Brown & Taylor, 2019).
Keywords: Psychological Realism; 19th-Century English Novel; Jane Austen; Charles Dickens; Narrative Techniques; Moral Complexity; Social Constraints; Literary Realism; Character Development; Psychological Depth in Fiction